Mahayana in Europe: Friedrich Max Müller and his Japanese interlocutors - Krämer, Hans Martin (Learning from the West, learning from the East, 2023)
Abstract Standard histories of the formation of Buddhism as an object of Western academic knowledge in the nineteenth century emphasize the discovery of Sanskrit and Pāli sources, as well as an originalist paradigm that sought to locate authentic Buddhism in the far Indian past and in the thought of its founder. As the Mahāyāna prevalent in East Asia was considered a secondary form of the religion, these standard accounts hastily conclude that Western scholars construed Buddhism without input from indigenous, and especially East Asian, voices. In contrast, this essay emphasizes the continued presence and influence of the Mahāyāna during the crucial period of the academic formation of Buddhist studies. This was true not just in terms of texts, but also through the presence of Mahāyāna Buddhists in Europe, especially Jōdo Shinshū priests and intellectuals who had come to Europe to acquire philological skills and historical knowledge. The encounter and lasting relationship between Max Müller and Nanjō Bun’yū serves as the main example of this, suggesting that knowledge on Buddhism in the nineteenth century was to a far greater extent a co-creation between European scholars and their Asian interlocutors than previous scholarship has admitted.
Gesehen am 25.09.2023